Inflammatory blood parameters as prognostic factors for surgical site infection after primary hip or knee arthroplasty: a systematic review protocol - Domecky, Petr; Rejman Patkova, Anna; Mala-Ladova, Katerina; Maly, Josef (BMJ open, 2021)
INTRODUCTION: Surgical site infection (SSI) is a potential complication of surgical procedure. SSI after implant surgery is a disaster both for patients and surgeons. Although predictive tools for SSI are available, none of them estimate early infection based on inflammatory blood parameters. The inflammatory process can be measured using several parameters including interleukin-6, C reactive protein, neutrophil to lymphocyte ratio, white cell count, erythrocyte sedimentation rate or procalcitonin. This systematic review aims to determine whether inflammatory blood parameters could be used as significant predictive factors for SSI after primary hip or knee arthroplasty. METHODS AND ANALYSIS: A systematic review of randomised controlled trials, cross-sectional studies, case-control studies and cohort studies, published in English, will be searched in the following electronic bibliographic databases: MEDLINE, Embase, PubMed, Cochrane Central Register of Controlled Trials and Web of Science. Studies performed in adult patients of all ages who underwent knee or hip arthroplasty, studies containing data on the risk/prognostic factors for preknee or postknee or hip arthroplasty SSI and studies with a minimum follow-up of 30 days after surgery will be included. A standardised form will be used to extract data from the included studies comprising study characteristics, participant characteristics, details of the intervention, study methodology and outcomes. Quality Assessment of Diagnostic Accuracy tool, second version, and Standards for Reporting of Diagnostic Accuracy Studies checklist will be used to assess risk of bias. Heterogeneity will be assessed using Cochran χ² statistic and I2 statistics where applicable. Grading of Recommendations Assessment, Development and Evaluation and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidance will be used to report findings. ETHICS AND DISSEMINATION: No ethics approval is required. The findings will be disseminated at national and international scientific sessions, also to be published in a peer-reviewed journal. PROSPERO REGISTRATION NUMBER: CRD42020147925.
Keywords: knee; Cross-Sectional Studies; hip; systematický přehled jako téma; Surgical Wound Infection; náhrada kyčelního kloubu; lidé; totální endoprotéza kolene; Arthroplasty, Replacement, Hip; Prognosis; infection control; infekce chirurgické rány; prognóza; Arthroplasty, Replacement, Knee; Systematic Reviews as Topic; Humans; průřezové studie; adult orthopaedics